Integration of Indonesian Capital Market and ASEAN Capital Market: A Study during the Covid-19 Pandemic - Linda Ariany Mahastanti; Ursula Brigitta Anggun Dwiandaru Oktavia (University of Merdeka Malang, 2022)
This research was conducted to examine the integration of the Indonesian capital market with the capital markets of other countries in ASEAN before and during the COVID-19 pandemic, so the results of this study are expected to provide an overview for investors in making investment decisions. Investment decision-making, especially in international diversification. The sample used in this study is the capital market index of Indonesia, Malaysia, Singapore, the Philippines, Thailand, and Vietnam. The analysis technique uses the Vector Error Correction Model (VECM). The analytical tool used is Eviews 11 software. The results show that there is proven integration between the Indonesian capital market and the capital markets of Malaysia, Singapore, the Philippines, Thailand, and Vietnam. In addition, this research also states that there is an increase in the integration of the Indonesian capital market with the capital markets that are members of the ASEAN Exchange, especially during the Covid-19 period.